Corrosion indicating coating

By using conductive materials and electrochromic materials in the coating, using weak current to induce fluorescence characteristics, the problem of difficult metal corrosion in traditional coatings is solved, real-time monitoring and early warning is achieved, maintenance costs are reduced and detection process is simplified.

CN119192942APending Publication Date: 2024-12-27CHINA SPECIAL EQUIP INSPECTION & RES INST
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202310760716.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-06-26
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

Traditional anticorrosion coatings are difficult to detect corrosion in real time on metal materials, lack early warning functions, high maintenance costs, and complex corrosion detection methods require professional knowledge.

Method used

The corrosion indicator coating is used to combine conductive materials and electrochromic materials to cause discoloration through weak currents, which intuitively reflects the corrosion conditions of metals. It uses materials such as conductive carbon fiber, nanocarbon black, barium aluminate, magnesium and europium to form fluorescence characteristics to show the corrosion conditions.

Benefits of technology

Real-time monitoring and early warning of metal corrosion is realized, the corrosion situation is visually displayed through color changes, reducing maintenance costs and simplifying the corrosion detection process.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention provides a corrosion indicating coating which comprises a conductive material and an electrochromic material, the conductive material comprises conductive carbon fibers, nano carbon black and graphene, and the electrochromic material comprises (Ba3-x-yMgxEuy) Al14O24. After metal under the coating is corroded, a weak current signal can be partially guided into the coating, the color-changing part is triggered to change color through current induction, and a user can observe whether the metal is corroded or not through the change of the color of the coating.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of coatings, and in particular, to a corrosion indicating coating. Background Art

[0003] Coating metal materials with traditional anti-corrosion coatings is one of the most widely used methods for metal corrosion protection. It has the advantages of simple construction, wide applicability, low cost, and easy combination with other protection methods. However, traditional anti-corrosion coatings mainly work through shielding, passivation or cathodic protection effects. Since they cover the surface of metal steel, the interface between air and metal steel is replaced by the interface between coating and steel, and it is difficult to obtain information on the internal steel surface. Therefore, when corrosion occurs, there is no significant phenomenon on the coating surface, and we cannot detect the occurrence of corrosion in the first time. The coating system does not have an early warning function. Moreover, once the coating system fails, the corrosion is already very serious, and the coating system basically no longer has a protective effect on the metal material, and the entire maintenance cost is extremely high. At the same time, in corrosion protection, the traditional way of detecting corrosion is generally electrochemical instruments and other equipment, which requires operators with a high level of knowledge to analyze and evaluate. The operation is extremely inconvenient and has strong limitations. Therefore, it is urgent to find a material that can actively provide corrosion early warning to solve this dilemma. Summary of the invention

[0004] In view of the shortcomings of the prior art, the present invention provides a corrosion indicating coating based on the principle of coating conductivity and current-induced color change. When the metal under the coating is corroded, a weak current signal can be partially introduced into the coating through a parallel connection, causing the color-changing part to change color through current induction.

[0005] The corrosion indicating coating provided by the present invention comprises a conductive material and an electrochromic material; the conductive material comprises one or more of conductive carbon fiber, nano carbon black and graphene, and the electrochromic material is (Ba 3-x-y Mg x Eu y )Al 14 O 24 , where x>0, y>0, x+y<3.

[0006] In some embodiments of the present invention, the content of the conductive material is 2-6%, and the (Ba 3-x-y Mg x Eu y )Al 14 O 24 The content is 0.5-1.5%.

[0007] In some embodiments of the present invention, the corrosion indicating paint is a two-component paint, wherein a first component includes the conductive material and the electrochromic material, and a second component includes a first solvent.

[0008] In some embodiments of the present invention, the first component further comprises a resin, a filler and a second solvent.

[0009] In some embodiments of the present invention, the resin includes epoxy resin and liquid petroleum resin.

[0010] In some embodiments of the present invention, the filler includes bentonite, titanium dioxide, talc and kaolin.

[0011] In some embodiments of the present invention, the second solvent includes xylene and n-butanol.

[0012] In some embodiments of the present invention, the first component includes: 25-30% epoxy resin, 1-3% liquid petroleum resin, 4-6% bentonite, 5-7% titanium dioxide, 27-33% talc, 13-17% kaolin, 1-3% short-cut conductive carbon fiber, 0.5-1.5% graphene, 0.5-1.5% nano carbon black, 0.5-1.5% (Ba 3-x-y Mg x Eu y )Al 14 O 24 , 4-6% xylene and 2.5-3.5% n-butanol.

[0013] In some embodiments of the present invention, the first solvent comprises: 40-60% xylene and 60-40% n-butanol.

[0014] In some embodiments of the present invention, when used, the dosage ratio of the first component to the second component is (3-5): (0.5-1.5).

[0015] The corrosion indicating coating provided by the present invention can intuitively reflect whether corrosion has occurred on the metal, and the user can observe whether corrosion has occurred on the metal through the change in the color of the coating.

[0016] Additional aspects and advantages of the present invention will be given in part in the following description and in part will be obvious from the following description, or will be learned through practice of the present invention. DETAILED DESCRIPTION

[0017] The specific embodiments of the present invention are described in more detail below so as to better understand the scheme of the present invention and its advantages in various aspects. However, the specific embodiments and examples described below are only for the purpose of illustration, rather than limitation of the present invention.

[0018] It is particularly important to point out that all similar substitutions and modifications are obvious to those skilled in the art and are considered to be included in the present invention. The methods and applications of the present invention have been described through preferred embodiments, and relevant personnel can obviously modify or appropriately change and combine the methods and applications described herein without departing from the content, spirit and scope of the present invention to implement and apply the technology of the present invention.

[0019] The corrosion indicating coating provided by the invention comprises a conductive material and an electrochromic material.

[0020] When metal corrodes, corrosion current is generated. In the present application, after the metal under the coating is corroded, a weak current is partially introduced into the interior of the coating under the action of the conductive material, causing the electrochromic material to change color. When the corrosion ends or stops, the color produced by the electrochromic material disappears. Therefore, the corrosion indicator coating provided by the present invention can reflect whether the metal has corroded.

[0021] The electrochromic material used in the present invention includes barium magnesium europium aluminate. Barium magnesium europium aluminate is a phosphor, which is a polyaluminate of barium magnesium (Ba 3-x-y Mg x Eu y )Al 14 O 24 , where x>0, y>0, x+y<3). When barium magnesium europium aluminate encounters the current generated by corrosion, it will produce blue fluorescence. Barium magnesium europium aluminate is a high-efficiency photoluminescent material. It emits a band spectrum with a peak wavelength of about 450nm under the excitation of 253.7nm ultraviolet light, and the quantum efficiency is close to 100%.

[0022] Barium magnesium europium aluminate will produce fluorescence characteristics under the action of electric current. Under the action of conductive materials, the amount of current passing through barium magnesium europium aluminate can be increased, which is helpful to stimulate the fluorescence characteristics of barium magnesium europium aluminate. In the present invention, the conductive material includes conductive carbon fiber, nano carbon black and graphene.

[0023] In polymer coatings, most materials are excellent insulators with a volume resistivity of up to 10 14 -10 20 Ω·cm, since a large number of polymer materials are used in the coating field, and the coating formula is prepared by blending, how to improve the conductivity of the coating becomes the key to this technology. Conductive carbon fiber, nano carbon black and graphene are used together, and a variety of ligands can enhance the bridging effect and reduce the resistance of the coating.

[0024] Nano carbon black is a fine spherical particle with a diameter of less than 30nm. It has good geometric filling properties and is dispersed in the matrix, becoming an auxiliary conductive phase, providing more "steps" for electron transitions. Under an external current, it can be polarized, thereby migrating, aggregating, and oriented. To a certain extent, it optimizes the space occupied by the conductive filler and improves the conductivity of the material. Increasing the amount of conductive filler added and reducing the particle size of the conductive filler are the best ways to improve the conductivity, but excessive filler addition and specific surface area will lead to filler agglomeration or internal defects in the material. This is because carbon black has a small particle size and is subject to less resistance from the matrix colloid. After polarization, the material is arranged in a chain along the axial direction of the electric field line through the attraction and repulsion between the charges, promoting the formation of a conductive path. At the same time, due to the effect of the electric field, nano-carbon black preferentially forms a conductive network along the axis of the electric field lines, which makes the electrons travel a shorter distance in the axis of the electric field lines. The transition of electrons along the normal direction of the electric field lines needs to partially pass through the axial conductive network and travel a longer distance, which makes the electrical properties of the composite material have a certain degree of anisotropy.

[0025] Graphene has excellent optical and electrical properties, and enhances the sensitivity of corrosion current. The carrier mobility of graphene at room temperature is about 15000cm 2 / (V·s), which is more than 10 times that of silicon and more than twice that of indium antimonide (InSb), the material with the highest known carrier mobility. Under certain specific conditions, such as low temperature, the carrier mobility of graphene can even reach 250,000 cm 2 / (V·s). The electron mobility of graphene is less affected by temperature changes. At any temperature between 50 and 500K, the electron mobility of a single layer of graphene is 15000cm 2 / (V·s). Due to the electric field induced molding, the volume resistivity of the coating is significantly lower than that of conventional conductive materials, and the graphene is oriented along the axis of the electric field line, thereby improving the conductive properties of the material.

[0026] Optionally, the conductive carbon fiber used in the present invention is a short-cut conductive carbon fiber, which is formed by chopped filaments through a fiber cutting machine. In some embodiments of the present invention, the properties of the conductive carbon fiber are shown in Table 1:

[0027] Table 1

[0028] Carbon content: more than 95% Tensile strength: 3530MPa Tensile modulus: 228GPa <![CDATA[Density: 1.75 g / cm 3 > Resistivity: 1.0-1.6Ωcm Fiber diameter: 7μm Cross-sectional shape: round <![CDATA[Bulk density: 0.4 g / cm 3 > Standard length: 3mm -

[0029] Optionally, the corrosion indicating paint is a two-component paint, wherein the first component includes the conductive material and the electrochromic material, and the second component includes a solvent. Two-component paint is also called two-pack paint or two-can paint, which refers to a paint in which the two components are packaged separately and the two components are mixed in an accurate proportion before use to solidify into a film.

[0030] Optionally, the first component also includes resin, filler and solvent. In order to distinguish, the present invention refers to the solvent of the second component as the first solvent, and the solvent of the first component as the second solvent. In the present invention, the first solvent and the second solvent can both include xylene and n-butanol. N-butanol and xylene are both organic solvents for coatings, wherein n-butanol has the effect of promoting coating leveling, can effectively improve the pH value, prevent solidification at low temperatures, allow the formation of a stable one-component formulation system, and play a role in thermosetting. Xylene can be added to reduce the viscosity of the resin, and because its volatilization rate matches the coating, the appearance of the paint film after coating can be guaranteed, while avoiding some drawbacks caused by construction, such as loss of gloss, orange peel, prickly heat, pinholes and other drawbacks.

[0031] Optionally, the resin includes epoxy resin and liquid petroleum resin. In the present invention, epoxy resin is used as a curing agent, and liquid petroleum resin is used as a film-forming agent.

[0032] Epoxy resin glue is waterproof and solvent-free. In addition to its superior bonding properties, it is also extremely durable and highly resistant to chemicals and heat. Epoxy resin is a petroleum-based adhesive that is clearly superior to paste glue when it comes to bonding things together. Epoxy resin contains the important ingredient epichlorohydrin, which forms a hard layer that is highly resistant to excessive cold, heat, and humidity. Epoxy resin only takes 6-30 minutes to cure. Due to its fast-drying properties, epoxy resin is an ideal material for bonding metal components. Liquid petroleum resin is packaged together with epoxy resin. The advantage is better dispersion performance, which can evenly mix and disperse the conductive material graphene and carbon fiber material, but the disadvantage is that the curing time is longer. Mixing the two resins can complement each other, while achieving fast-drying properties and improving material dispersion.

[0033] Optionally, the filler includes bentonite, kaolin, titanium dioxide and talc. In the present invention, these fillers play a synergistic role, wherein the mixture of bentonite and kaolin can increase the specific surface area, effectively prevent the coating from settling, and play a role in stabilizing the suspension. Titanium dioxide and talc can improve the dispersion performance of graphene in the coating and improve the conductivity.

[0034] When the corrosion indicating coating of the present application is used, the usage ratio of the first component to the second component is preferably (3-5):(0.5-1.5), and more preferably the usage ratio is 4:1.

[0035] In some embodiments of the present invention, the first component may include: 25-30% epoxy resin, 1-3% liquid petroleum resin, 4-6% bentonite, 5-7% titanium dioxide, 27-33% talc, 13-17% kaolin, 1-3% chopped conductive carbon fiber, 0.5-1.5% graphene, 0.5-1.5% nano carbon black, 0.5-1.5% barium magnesium europium aluminate, 4-6% xylene and 2.5-3.5% n-butanol. The first solvent of the second component may include: 40-60% xylene and 60-40% n-butanol.

[0036] The present invention is described below with reference to specific embodiments. The process condition values ​​taken in the following embodiments are all exemplary, and the possible value ranges are as shown in the above invention content. For process parameters not specifically noted, conventional techniques can be used. The detection methods used in the following embodiments are all conventional detection methods in the industry. Unless otherwise specified, the reagents and instruments used in the technical solutions provided by the present invention can be purchased from conventional channels or the market.

[0037] Preparation Example 1

[0038] This preparation example provides a corrosion indicating coating. The first component includes: 30 parts of epoxy resin, 2 parts of liquid petroleum resin, 6 parts of bentonite, 6 parts of titanium dioxide, 29 parts of talc, 15 parts of kaolin, 2 parts of short-cut conductive carbon fiber, 1 part of graphene, 1 part of nano carbon black, 1 part of barium magnesium europium aluminate, 5 parts of xylene, and 2 parts of n-butanol. The second component includes: 60% xylene and 40% n-butanol.

[0039] The preparation process is as follows:

[0040] 1) Prepare the first component

[0041] Step 1: Weigh bentonite, titanium dioxide, talc, kaolin, chopped conductive carbon fiber, graphene, nano carbon black and barium magnesium europium aluminate according to the components and mix them evenly.

[0042] Step 2: Mix the two liquids, xylene and n-butanol, evenly by stirring at a slow speed of less than 300 rpm.

[0043] Step 3: Add the components in step 1 to step 2, stir at 500 rpm for 20 minutes until it becomes a paste, then add epoxy resin and liquid petroleum resin and continue to stir at 1000-1500 rpm, filter with a 150-mesh filter and put into a barrel. After stirring evenly, let it stand for use.

[0044] 2) Prepare the second component

[0045] Weigh xylene and n-butanol according to the components and mix them evenly.

[0046] Example 1

[0047] The corrosion indicating coating prepared in Preparation Example 1 was mixed with the first component and the second component in a ratio of 4:1 and then coated on the same steel pipe as in Comparative Example 1. At this time, the coating surface was white. Then, the corrosion test was carried out in the same environment.

[0048] The test results showed that from the 7th day, some areas of the paint surface showed fluorescence. On the 9th day, the paint fluorescence increased to the strongest.

[0049] After the steel pipe was taken out on the 12th day, the color of the coating surface returned to white.

[0050] Comparative Example 1

[0051] Select a carbon steel pipe with a length of 5cm, an inner diameter of 15mm, and an outer diameter of 20mm, and clean the base surface: clean the rust, weld skin, welding spatter, oil stains, dust and other debris on the part to be painted. Metal color sandblasting and shot blasting.

[0052] The cleaned carbon steel pipe was placed in a 3.5% NaCl solution and the pH value was adjusted to about 2.0 with acetic acid for corrosion immersion test. The test results showed that the steel pipe began to corrode on the third day, and on the seventh day, obvious surface iron oxide products appeared on the steel pipe, and the local surface of the steel pipe was reddish brown, indicating that corrosion had already progressed.

[0053] The steel pipe was taken out on the 12th day (ie no corrosion test was performed).

[0054] Comparative Example 2

[0055] The corrosion indicator coating used in this comparative example is different from that in Preparation Example 1 in that the first component is composed of 30 parts of epoxy resin, 2 parts of liquid petroleum resin, 6 parts of bentonite, 6 parts of titanium dioxide, 29 parts of talc, 15 parts of kaolin, 5 parts of barium magnesium europium aluminate, 5 parts of xylene, and 2 parts of n-butanol. The second components are the same.

[0056] The first component and the second component were mixed in a ratio of 4:1 and then coated on the same steel pipe as in Comparative Example 1. The coating surface was white at this time. Then, the coating was placed in the same environment for a corrosion immersion test.

[0057] The test results show that the paint surface shows light blue from the second day, and the steel pipe surface turns bright blue on the fifth day.

[0058] After the steel pipe was taken out on the 12th day, the color of the coating surface returned to reddish brown.

[0059] It can be seen from the above embodiments and comparative examples that the corrosion indicating coating provided by the present invention can produce fluorescence characteristics after the metal under the coating is corroded, reflecting that the metal has been corroded, and can reflect the degree of corrosion through the change of the fluorescence effect. And it can return to the original color when the corrosion is over.

[0060] Obviously, the above embodiments are merely examples for clearly explaining the present invention, and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived therefrom are still within the protection scope of the present invention.

Claims

1. A corrosion indicating coating, characterized in that: It includes a conductive material and an electrochromic material; the conductive material includes conductive carbon fiber, nano carbon black and graphene, and the electrochromic material includes (Ba 3-x-y Mg x Eu y )Al 14 O 24 , where x>0, y>0, x+y<3.

2. The corrosion indicating coating according to claim 1, characterized in that: The content of the conductive material is 2-6%, and the (Ba 3-x-y Mg x Eu y )Al 14 O 24 The content is 0.5-1.5%.

3. The corrosion indicating coating according to claim 1, characterized in that: The corrosion indicating paint is a two-component paint, wherein the first component includes the conductive material and the electrochromic material, and the second component includes a first solvent.

4. The corrosion indicating coating according to claim 3, characterized in that: The first component also includes a resin, a filler, and a second solvent.

5. The corrosion indicating coating according to claim 4, characterized in that: The resins include epoxy resins and liquid petroleum resins.

6. The corrosion indicating paint according to claim 4, characterized in that: The fillers include bentonite, titanium dioxide, talc and kaolin.

7. The corrosion indicating paint according to claim 4, characterized in that: The second solvent includes xylene and n-butanol.

8. The corrosion indicating paint according to claim 4, characterized in that: The first component includes: 25-30% epoxy resin, 1-3% liquid petroleum resin, 4-6% bentonite, 5-7% titanium dioxide, 27-33% talc, 13-17% kaolin, 1-3% short-cut conductive carbon fiber, 0.5-1.5% graphene, 0.5-1.5% nano carbon black, 0.5-1.5% (Ba 3-x-y Mg x Eu y )Al 14 O 24 , 4-6% xylene and 2.5-3.5% n-butanol.

9. The corrosion indicating paint according to claim 3, characterized in that: The first solvent comprises: 40-60% xylene and 60-40% n-butanol.

10. The corrosion indicating paint according to claim 3, characterized in that: When used, the dosage ratio of the first component to the second component is (3-5): (0.5-1.5).